South Asia development and cooperation report 2008 - Research and Information System for Developing Countries (New Delhi, 2008)
The South Asian countries have undertaken major reforms of their trade and investment regimes since early 1990s. As a result the region's economies today are far more integrated with the world economy than earlier, not only in terms of trade and investment linkages but also in terms of the growing integration of capital markets. This Report examines the prospects of this global economic integration for the South Asian economies. It highlights how the process of global economic integration enables these economies to benefit from the emerging international specialization and division of labour and allows them to absorb the spillovers of knowledge creation in different parts of the world. The report also reviews the downside risks to the growth outlook. It focuses on the importance of regional economic cooperation in Asia in addressing the emerging global challenges.
Keywords: Report-global economy